The Correlation Between Weight Gain and Diet With Gestational Hypertension at Montong Health Center, Tuban, East Java - Hurin'in, Nur Maziyah; Keswati, Wiwik Duwi (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Introduction. Hypertension in pregnant women can cause blood vessels to narrow so that the blood supply to the body's tissues decreases resulting in organs not functioning as they should. The consequences that can appear in the mother are respiratory disorders, HELLP syndrome, cardiovascular disorders, liver disorders, which can eventually result in maternal death. In the fetus, it can cause Intra Uterine Growth Retardation (IUGR), premature fetus, low birth weight and death. Methods. This was a correlational research with a cross sectional time approach. The population in this research was all TM II pregnant women at the Montong Health Center, which totals 40 respondents. The sample in this case was 36 respondents who met the inclusion criteria and exclusion criteria. The sampling technique used was simple random sampling. The bivariate analysis of the statistical test used was Spearman Test, then the data was analyzed using the SPSS program with an error level of 0.05. Results. There was a statistically significant moderate correlation between weight gain and gestational hypertension (Spearman's ρ = 0.448, p = 0.006) and a very strong and statistically significant correlation was found between dietary patterns and gestational hypertension (Spearman's ρ = 0.673, p = 0.000). Conclusion. Weight gain and diet are significant risk factors for gestational hypertension, and implementing daily digital lifestyle monitoring could be an innovative approach to prevent its occurrence during pregnancy